2005
DOI: 10.1105/tpc.105.030973
|View full text |Cite
|
Sign up to set email alerts
|

The Rice brassinosteroid-deficient dwarf2 Mutant, Defective in the Rice Homolog of Arabidopsis DIMINUTO/DWARF1, Is Rescued by the Endogenously Accumulated Alternative Bioactive Brassinosteroid, Dolichosterone

Abstract: We have identified a rice (Oryza sativa) brassinosteroid (BR)-deficient mutant, BR-deficient dwarf2 (brd2). The brd2 locus contains a single base deletion in the coding region of Dim/dwf1, a homolog of Arabidopsis thaliana DIMINUTO/DWARF1 (DIM/DWF1). Introduction of the wild-type Dim/dwf1 gene into brd2 restored the normal phenotype. Overproduction and repression of Dim/dwf1 resulted in contrasting phenotypes, with repressors mimicking the brd2 phenotype and overproducers having large stature with increased nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
219
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 269 publications
(225 citation statements)
references
References 43 publications
4
219
0
2
Order By: Relevance
“…Causal genes of small (or short) seed phenotype have been identified by us and other research groups through map-based cloning, namely D1 (also named RGA1) encoding the heterotrimeric G protein α subunit (Ashikari et al, 1999;Fujisawa et al, 1999), D11 encoding a cytochrome P450 involved in brassinosteroid (BR) biosynthesis (Tanabe et al, 2005), BRD1 and D2 encoding different types of cytochrome P450 that are also involved in BR synthesis (Hong et al, 2002(Hong et al, , 2003, BRD2 (also named rice Dim/dwf1) encoding an enzyme associated with BR biosynthesis (Hong et al, 2005), D61 (also named OsBRI1) encoding a BR receptor (Yamamuro et al, 2000), and finally SRS3 encoding the kinesin 13 protein (Kitagawa et al, 2010). These studies have shown that both the heterotrimeric G protein signaling pathway and the BR signaling pathway play a major role in the regulation of seed size.…”
Section: Introductionmentioning
confidence: 99%
“…Causal genes of small (or short) seed phenotype have been identified by us and other research groups through map-based cloning, namely D1 (also named RGA1) encoding the heterotrimeric G protein α subunit (Ashikari et al, 1999;Fujisawa et al, 1999), D11 encoding a cytochrome P450 involved in brassinosteroid (BR) biosynthesis (Tanabe et al, 2005), BRD1 and D2 encoding different types of cytochrome P450 that are also involved in BR synthesis (Hong et al, 2002(Hong et al, , 2003, BRD2 (also named rice Dim/dwf1) encoding an enzyme associated with BR biosynthesis (Hong et al, 2005), D61 (also named OsBRI1) encoding a BR receptor (Yamamuro et al, 2000), and finally SRS3 encoding the kinesin 13 protein (Kitagawa et al, 2010). These studies have shown that both the heterotrimeric G protein signaling pathway and the BR signaling pathway play a major role in the regulation of seed size.…”
Section: Introductionmentioning
confidence: 99%
“…Mutants with deficiencies of brassinosteroid (BR) biosynthetic genes, dwarf4-1 (Sakamoto et al, 2006), ebisu dwarf (d2; Hong et al, 2003), and chromosome segment deleted dwarf1 , show reduced leaf inclination, which also is observed in the BR signalingdefective mutant d61 (Yamamuro et al, 2000) or transgenic rice plants with suppressed expression of OsBAK1 ) and OsBZR1 (Bai et al, 2007). On the other hand, transgenic rice plants overexpressing sterol C-22 hydroxylase (an important enzyme of BR biosynthesis; Wu et al, 2008), OsDim/dwf1 (which participates in late steps of sterol biosynthesis; Hong et al, 2005), and OsBAK1 ) present increased leaf inclination, which is consistent with BR promoting cell elongation at the adaxial side of the lamina joint (Cao and Chen, 1995). A recent study showed that BR signaling inhibits the proliferation of sclerenchyma cells at the abaxial side of the lamina joint by coordinately regulating the U-type cyclin CYCU4;1 (Sun et al, 2015).…”
mentioning
confidence: 99%
“…Although this phenotype has been confirmed independently in several mutants harboring the d1, d2, d11, d61, brd1 and brd2 genes (Takahashi and Takeda 1970, Takeda 1974, Ashikari et al 1999, Fujisawa et al 1999, Wu et al 1999a, Yamamuro et al 2000, Hong et al 2002, Hong et al 2003, Hong et al 2005, Tanabe et al 2005, the use of these mutant genes in rice breeding has not been reported, presumably for the Communicated by M. Yano Received October 3, 2005. Accepted April 17, 2006 following reasons.…”
Section: Introductionmentioning
confidence: 99%